Using carboxyfluorescein diacetate succinimidyl ester to monitor intracellular protein glycation - Boucher, Julie; Simard, Élie; Froehlich, Ulrike; D’Orléans-Juste, Pedro; Grandbois, Michel (Analytical biochemistry, 2015)
Protein glycation is a ubiquitous process involved in vascular complications observed in diabetes. Glyoxal (GO), an intracellular reactive oxoaldehyde that is one of the most potent glycation agents, readily reacts with amines present on proteins to produce the lysine-derived adduct carboxymethyllysine, which is a prevalent advanced glycation end-product (AGE). Our group previously showed that cell exposure to GO leads to an alteration in the cell contractile activity that could occur as a result of the glycation of various proteins regulating the cell contractile machinery. Here, we measured the extent of glycation on three functionally distinct proteins known to participate in cell contraction and cytoskeletal organization—Rho-kinase (ROCK), actin, and gelsolin (GSN)—using an assay based on the reaction of the cell membrane-permeable fluorescent probe carboxyfluorescein diacetate succinimidyl ester (CFDA–SE), which reacts with primary amine groups of proteins. By combining CFDA–SE fluorescence and Western blot detection, we observed (following GO incubation) increased glycation of actin and ROCK as well as an increased interaction between actin and GSN as observed by co-immunoprecipitation. Thus, we conclude that the use of the fluorescent probe CFDA–SE offers an interesting alternative to perform a comparative analysis of the extent of intracellular protein glycation in live cells.